Standardized Reporter Systems for Purification and Imaging of Human Pluripotent Stem Cell-derived Motor Neurons and Other Cholinergic Cells. (1st December 2020) - Garcia-Diaz, Alejandro; Efe, Gizem; Kabra, Khushbu; Patel, Achchhe; Lowry, Emily R.; Shneider, Neil A.; Corneo, Barbara; Wichterle, Hynek
Highlights: New set of human HB9 and VACHT targeted iPSC reporter lines for purification of motor neurons and other cholinergic neurons. The Cre-lox amplification of reporter expression is compatible with live-imaging and long-term culture studies. Cre based reporters expressing CD14 receptor are useful for motor neuron purification at scale. Abstract: Reliable and consistent pluripotent stem cell reporter systems for efficient purification and visualization of motor neurons are essential reagents for the study of normal motor neuron biology and for effective disease modeling. To overcome the inherent noisiness of transgene-based reporters, we developed a new series of human induced pluripotent stem cell lines by knocking in tdTomato, Cre, or CreERT2 recombinase into the HB9 (MNX1) or VACHT (SLC18A3) genomic loci. The new lines were validated by directed differentiation into spinal motor neurons and immunostaining for motor neuron markers HB9 and ISL1. To facilitate efficient purification of spinal motor neurons, we further engineered the VACHT-Cre cell line with a validated, conditional CD14-GFP construct that allows for both fluorescence-based identification of motor neurons, as well as magnetic-activated cell sorting (MACS) to isolate differentiated motor neurons at scale. The targeting strategies developed here offer a standardized platform for reproducible comparison of motor neurons across independently derived pluripotent cell lines.